2021
DOI: 10.1007/s00380-021-01793-3
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative frailty affects postoperative complications, exercise capacity, and home discharge rates after surgical and transcatheter aortic valve replacement

Abstract: Assessment of frailty is important for risk stratification among the elderly with severe aortic stenosis (AS) when considering interventions such as surgical aortic valve replacement (SAVR) or transcatheter aortic valve replacement (TAVR). However, evidence of the impact of preoperative frailty on short-term postoperative outcomes or functional recovery is limited. This retrospective study included 234 consecutive patients with severe AS who underwent SAVR or TAVR at Kobe University Hospital between Dec 2013 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…A key finding was that frailty status did not impact 6MWT performance following surgery. They found that the SAVR group, regardless of frailty, declined significantly, whereas the TAVR group's 6MWT decline did not reach statistical significance [20]. These results suggest that our subjects possibly had higher pre-operative measures as well.…”
Section: Discussionmentioning
confidence: 64%
“…A key finding was that frailty status did not impact 6MWT performance following surgery. They found that the SAVR group, regardless of frailty, declined significantly, whereas the TAVR group's 6MWT decline did not reach statistical significance [20]. These results suggest that our subjects possibly had higher pre-operative measures as well.…”
Section: Discussionmentioning
confidence: 64%
“…The first study found a lower likelihood of discharge to a home location for patients with preoperative frailty, independent of the tool used (CHS vs. Study of Osteoporotic Fractures [SOF]) 14 . The second study also found frailty to be associated with a non‐home discharge location, with an adjusted OR of 0.1 (0.06–0.29) 22 . The third study did not find a statistically significant association, and reported an OR of 0.8 (0.3–1.8) 18 .…”
Section: Resultsmentioning
confidence: 98%
“…Patients were enrolled between 2007 and 2019. Seven studies were performed in North America, 13–19 two in Europe, 20,21 and one in Asia 22 . All studies were cohort studies, seven being prospective 13–15,17,19–21 and three being retrospective 16,18,22 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations